UNGKAPAN VERBAL DAN NONVERBAL BERMAKNA BUDAYA DALAM TARI TUMATENDEN MASYARAKAT TONSEA MINAHASA : KAJIAN LINGUISTIK ANTROPOLOGI - Mangangue, Jeane (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Language used by humans to interact with each other so that language evolved in with the wearer’s cultural development. Like a human being to plan and create a culture of continuous, language as part of the culture also continues to grow as the dynamics of human cultural development. The method which used in data collection that is observation with tapping technique and listening attentively, involving, talking technique and also listening attentively, free involving talking technique, interview method was carried out in two ways namely unfocused interview and focused interview. Interview method to informant was carried out by using the concept of Spradley ethnographic questions. To analyze data was used concept of expression analysis, linguistic anthropology analysis and the concept of Dell Hymes through acronym of speaking. The results showed that the verbal expressions in Tumatenden dance consist of four parts, namely 1) part of meeting, 2) part of living together, 3)part of separation, and 4) part of meeting again, the nonverbal expressions consist of gestures and attributes that are imposed.The meeting is related to the cultural contexts that exist in Tonsea society.